Insurance Activity by Social Economy Companies: A Critical Review of the Situation in Spain - Puyalto Franco, María José (2019)
Social Economy companies constitute not only a particularly valuable legal instrument to empower workers and consumers in a digital and globalised market, but they are also a clear alternative to profit-making companies. Although Spain was a pioneer by recognising this sector in the Law 5/2011, of March 29th, of Social Economy, the main criticism lies in the lack of application of the framework, in general, and the measures of the Seventh Additional Provision, in particular. These measures called for the review of specific legislation in order to remove the limitations to Social Economy entities so that they could operate in any economic activity without any unjustified barrier. However, the Spanish legislator has not made any extra or systematic effort to reach that end. Therefore, this academic work will address the consequences of this inaction concerning the Social Economy companies that operate in a highly regulated sector: the insurance market.